Information seeking tool based on learning style / Nor Liyana Binti Mohd Shuib - Nor Liyana, Mohd Shuib (2013)
Learning is enhanced when its activities are aligned with learning style. An integral component of students’ learning activities is searching for and retrieving reading materials. However, it is not always easy to find suitable reading materials that match the students’ needs. This is mainly because most search engines are built with only content in mind. This study investigates students’ learning needs in information seeking, in relation to their learning styles. This involves identifying students’ information seeking behaviour from a literature review and preliminary studies. It was found that the reading materials retrieved using current information seeking tools do not match students’ learning styles. Thus, this research aims to develop an information seeking tool that considers students' learning style within its retrieval process. The development of such a tool requires the reading materials to be classified based on learning style preferences. Primitive elements, such as text, graphs, and diagrams, have been chosen as identifiers for the above classification. An information seeking tool, with learning style consideration, was then proposed. A prototype was developed to map and match reading materials to students’ learning styles. For the evaluation, experiments and surveys were conducted, and the results obtained were then analysed. Our findings show that this new information seeking tool is able to find reading materials that are more closely related to the students’ individual learning styles.